Using Social Justice Pedagogies to Improve Student Numeracy in Secondary School Education - Voss, R.; Rickards, Anthony (IISTE, 2016)
This unique Australian paper presents a study involving a Western Victorian District High School year nine mathematics class using social justice pedagogy to learn Mathematics. The class was comprised of gifted students, mainstream students and students who had diagnosed learning disabilities, all key foci in Australian Education research. The learning content of the Mathematics unit required students to make comparisons between their own lifestyles and those of different families from around the world. This was socially and educationally important as Mathematics was used as a tool to investigate social inequality to improve numeracy. One aim of the study was to determine if there are associations between student learning, student engagement and student achievement when teaching mathematics using social justice pedagogies. The findings from this study suggest that when mathematics is taught using Social Justice Pedagogy, student learning and engagement are both improved.